2012
DOI: 10.1007/s12639-012-0099-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of three indigenous strains of entomopathogenic nematodes from Meghalaya, India against mustard sawfly, Athalia lugens proxima Klug (Hymenoptera: Tenthredinidae)

Abstract: The objective of this study was to evaluate the efficacy of three indigenous strains of entomopathogenic nematodes (EPN) from Meghalaya, India, namely Heterorhabditis indica Poinar, Karunakar and David, Steinernema thermophilum Ganguly and Singh, and Steinernema glaseri (Steiner) against the last instar larva of mustard sawfly, Athalia lugens proxima Klug, a serious pest of mustard and radish in India. The larvae of A. lugens proxima were exposed to 10, 25, 50, 75 and 100 infective juveniles (IJs) concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…However, progeny production assay revealed H. indica was significantly greater than that of S. feltiae, S. carpocapsae, S. glasseri, S. abbassi. Moreover, our results of progeny production agree with the data of Mannion and Jansson (1992); Yadav and Lalramliana 2012;Gowda et al (2016) and Patil et al (2016). One possible reason for this difference in EPNs progeny production in M. domestica, may be related to the type of reproduction of Heterorhabditids.…”
Section: Discussionsupporting
confidence: 89%
“…However, progeny production assay revealed H. indica was significantly greater than that of S. feltiae, S. carpocapsae, S. glasseri, S. abbassi. Moreover, our results of progeny production agree with the data of Mannion and Jansson (1992); Yadav and Lalramliana 2012;Gowda et al (2016) and Patil et al (2016). One possible reason for this difference in EPNs progeny production in M. domestica, may be related to the type of reproduction of Heterorhabditids.…”
Section: Discussionsupporting
confidence: 89%
“…themophilum and 8.0–25.0% for S . glaseri [ 45 ]. This indicates that each species of EPN responds to different levels of moisture.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also demonstrated this reduction in nematode reproduction at the highest rates of Steinernema sp. (640 IJ/insect), of S. feltiae (Filipjev, 1934) (200-400 IJ/insect), and of S. thermophilum (100 IJ/insect) for larva of Tenebrio molitor (L.) (Baliadi et al 2011), G. mellonella (Rahoo et al 2017), and Athalia lugens proxima (Yadav and Lalramliana 2012), respectively. According to these studies, Correspondences: samanta.nanzer@gmail.com and garrigos.leite@gmail.com the rate that start causing a decrease in nematode reproduction depend on the susceptibility of the host.…”
Section: Discussionmentioning
confidence: 99%